The Application of Serum Cortisol Level for Diagnosis and Guideline for Diagnosed Adrenal Insufficiency - Wittayapraparat, Pakorn (Journal of Health Science of Thailand, 2017)
Serum cortisol was used for diagnosis of adrenal insufficiency, assess the Hypothalamic- Pituitary-Adrenal axis (HPA axis) and diagnosis of Cushing's syndrome. The serum cortisol level can be done in a general hospital. This retrospective descriptive analysis reviewed 62 patient records of medicine department of Chasoengsao hospital between October 1 and December 31, 2007. In 62 patients, 20 men and 42 women, 8 patients had serum cortisol ≤ 5 ug/dl and 37 patients had serum cortisol ≥ 18 ug/dl. Within 24 hours before blood sampling 10 patients received hydrocortisone. Of the 28 patients whose blood sample were drawn during severe stress, 20 patients had serum cortisol ³ 18 ug/dl and ≤ 5 ug/dl in only one patient. Serum cortisol was checked between 6- 8 am in 28 patients and 18 patients was checked at any time. This paper describes and recommends guideline for checking and interpret serum cortisol for diagnosis and treatment relevant to adrenal insufficiency.